Elucidation of the Burkholderia cenocepacia hopanoid biosynthesis pathway uncovers functions for conserved proteins in hopanoid‐producing bacteria. (24th June 2014) - Schmerk, Crystal L.; Welander, Paula V.; Hamad, Mohamad A.; Bain, Katie L.; Bernards, Mark A.; Summons, Roger E.; Valvano, Miguel A.
Summary: Hopanoids are bacterial surrogates of eukaryotic membrane sterols and among earth's most abundant natural products. Their molecular fossils remain in sediments spanning more than a billion years. However, hopanoid metabolism and function are not fully understood. B urkholderia species are environmental opportunistic pathogens that produce hopanoids and also occupy diverse ecological niches. We investigated hopanoids biosynthesis in B urkholderia cenocepacia by deletion mutagenesis and structural characterization of the hopanoids produced by the mutants. The enzymes encoded by hpnH and hpnG were essential for production of all C35 extended hopanoids, including bacteriohopanetetrol (BHT), BHT glucosamine and BHT cyclitol ether. Deletion of hpnI resulted in BHT production, while Δ hpnJ produced only BHT glucosamine. Thus, HpnI is required for BHT glucosamine production while HpnJ is responsible for its conversion to the cyclitol ether. The Δ hpnH and Δ hpnG mutants could not grow under any stress condition tested, whereas Δ hpnI, Δ hpnJ and Δ hpnK displayed wild‐type growth rates when exposed to detergent, but varying levels of sensitivity to low pH and polymyxin B. This study not only elucidates the biosynthetic pathway of hopanoids in B . cenocepacia, but also uncovers a biosynthetic role for the conserved proteins HpnI, HpnJ and HpnK in other hopanoid‐producing bacteria.